История одного эвфемизма - Ушинскене, Виктория (Slavistica Vilnensis, 2002)
The article analyses the history and semantic evolution of the Russian word xep, a Church Slavonic borrowing meaning the Cyrillic letter χ. For several centuries, the word was also used in Russian as an euphemism for a phoneticallysimilar obscene term of abuse. The orthographic reform of 1918 replaced the old name for the letter χ. For this reason, the word xep lost its original meaning in the 20th century, and gradually developed from a euphemism into an obscenity in its own right.